Ultrasound-guided percutaneous microwave ablation for locoregional recurrence of medullary thyroid carcinoma - Isa Cam; Almotasem Shatat; Damla Köksalan; Said Atış; Ahmet Yalnız; Özgür Çakır; Alev Selek; Mehmet Sözen; Büşra Yaprak Bayrak; Seda Öztürk; Özge Telci Çakıllı; Nuh Zafer Cantürk; et al. (International Journal of Hyperthermia)
Objective Medullary thyroid carcinoma (MTC) is a rare, aggressive thyroid malignancy with frequent locoregional recurrence rate at 30–50%. Reoperative neck surgery is standard but challenging and risky. Ultrasound (US)-guided microwave ablation (MWA) offers minimally invasive alternatives, though evidence in recurrent MTC remains limited. This study evaluated the efficacy and safety of percutaneous US-guided MWA for treating recurrent MTC.Methods A retrospective review included 22 patients with biopsy-proven locoregional recurrent MTC treated by US-guided percutaneous MWA after prior total thyroidectomy. All were either poor surgical candidates or declined reoperation. Thirty-four lesions underwent single-session outpatient ablation. Tumor size, serum calcitonin and volume reduction ratio (VRR) were assessed at baseline, 1, 3, 6 and 12 months post-ablation. Imaging and biochemical responses determined treatment outcomes. Recurrence-free survival between recurrent and non-recurrent groups was compared.Results A total of 22 patients (median age 52 years; 14% hereditary) were included and MWA was successfully performed in all. Mean tumor diameter significantly reduced from 14.3 ± 11.6 mm to 2.6 ± 3.4 mm at 12 months (p < .001). Median serum calcitonin decreased significantly from 1165 pg/mL to 108 pg/mL at 12 months (p < .001). Treated lesions showed no regrowth; however, 50% developed new metastases elsewhere, correlating with higher initial metastatic burden (p = .001) and higher baseline calcitonin (p = .037).Conclusion US-guided MWA effectively reduces tumor volume and calcitonin levels in recurrent MTC with minimal morbidity, though close surveillance for new metastases remains essential.